Memahami Konsep Statistika (Pemusatan Data: Mean, Median, dan Modus) dalam Kehidupan Sehari-hari Menggunakan Pendekatan PMRI - Hulva Sari; Monica Putri Pratiwi; Syutaridho Syutaridho (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to determine the role of statistics in everyday life to help students understand the concept of data centering measures, especially the mean, median and mode. This research was conducted at MTS Aisyiyah Palembang. The research subjects were class VIII students, involving 16 students who were divided into 3 groups. This research used the PMRI approach where students were invited to measure contextually their height. The results showed that the PMRI approach can help students discover for themselves how to calculate a person's height and find the mean, median and mode through a mathematical reference process. Finding their own concept of data centering measures and solving problems in everyday life related to the concept of data centering measures. The results of this study show that through a series of activities that have been carried out help students in learning the size of data concentration.